2016
DOI: 10.1002/cbin.10618
|View full text |Cite
|
Sign up to set email alerts
|

Basal neutrophil function in human aging: Implications in endothelial cell adhesion

Abstract: Much attention has been drawn to the pro-inflammatory condition that accompanies aging. This study compared parameters from non-stimulated neutrophils, obtained from young (18-30 years old [y.o.]) and elderly (65-80 y.o.) human volunteers. Measured as an inflammatory marker, plasmatic concentration of hs-CRP was found higher in elderly individuals. Non-stimulated neutrophil production of ROS and NO was, respectively, 38 and 29% higher for the aged group. From the adhesion molecules evaluated, only CD11b expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Phenotypically, up-regulation of CD45, TLR4, CD24, CXCR4, CD11b, CD11c, CD49d, ICAM and down-regulation of CXCR2, CD62L, L-lectin, LY6C/G have been documented in aged human neutrophils ( 156 , 165 ). In addition, altered cytokines secretion profiles, generation of reactive oxygen species (ROS) and associated microbial killing have been reported, although these findings might largely be stimulus-dependent ( 28 , 166 , 167 ). Age dependent impaired formation of neutrophil extracellular traps (NETs), structures able to capture and immobilize pathogens, may explain why older adults are more susceptible to invasive bacterial infections ( 29 , 168 , 169 ).…”
Section: Age-associated Immune Cell Dysfunctionsmentioning
confidence: 99%
“…Phenotypically, up-regulation of CD45, TLR4, CD24, CXCR4, CD11b, CD11c, CD49d, ICAM and down-regulation of CXCR2, CD62L, L-lectin, LY6C/G have been documented in aged human neutrophils ( 156 , 165 ). In addition, altered cytokines secretion profiles, generation of reactive oxygen species (ROS) and associated microbial killing have been reported, although these findings might largely be stimulus-dependent ( 28 , 166 , 167 ). Age dependent impaired formation of neutrophil extracellular traps (NETs), structures able to capture and immobilize pathogens, may explain why older adults are more susceptible to invasive bacterial infections ( 29 , 168 , 169 ).…”
Section: Age-associated Immune Cell Dysfunctionsmentioning
confidence: 99%
“…Adhesion is reported to be unchanged or slightly increased, thus reducing chemotaxis. The increases in the expression of neutrophil adhesion molecules CD11b and CD15 in aged subjects [ 107 , 108 ] are likely to enhance neutrophil adhesion to endothelial cells and contribute to the impaired chemotaxis, as observed in neutrophils of aged patients. Besides the increased number of lung neutrophils, their function also is partly impaired in aging.…”
Section: Age-associated Changes In Pulmonary Structure and (Immunementioning
confidence: 99%
“…Besides the increased number of lung neutrophils, their function also is partly impaired in aging. Basal ROS and NO production are increased in neutrophils from aged donors [ 108 ]. Conflicting data exist concerning the ability of neutrophils from aged patients to produce ROS in response to diverse external stimuli.…”
Section: Age-associated Changes In Pulmonary Structure and (Immunementioning
confidence: 99%
“…Neutrophils from older mice and humans are less able to phagocytose and kill pathogens intracellularly compared with those from younger hosts [89,115,116,[140][141][142][143][144][145], which may be due to factors such as altered actin polymerization, changes in bioenergetics, or reductions in the expression of critical phagocytosis receptors [47,115,146]. Interestingly, unstimulated neutrophils from older human subjects exhibit higher ROS levels than do those from younger subjects, and the enhanced production of ROS might be responsible for age-associated damage to the vascular endothelium [147]. Furthermore, another study suggests the observed basal, hyperactivated state of neutrophils in aged mice (i.e., increased ROS production) might be due to microbiomederived signals that change with age [148].…”
Section: Neutrophilsmentioning
confidence: 99%